Effect of Time and Steam Pressure on Gelatinization of Starch and Antioxidant Properties of Curcumin of Turmeric (Curcuma Longa) Rhizomes - Wasiya Farzana; Ashitha G. N.; Eresh Kumar Kuruba; D. Amirtham (International Journal of Economic Plants)
Turmeric grown in state of Tamil Nadu in India was analysed for its change in Curcumin content when subjected to varying pressures of steam during pressurised steam boiling under laboratory scale conditions.The same were tested in the field for optimized conditions in the already existing turmeric boiling system with the farmers, the locally available parboiling drum used for paddy parboiling and the improved steam boiling vessel developed at Tamil Nadu Agricultural University.The varying pressures which brought about varying degrees of gelatinization of starch which in turn affecting the Curcumin content were studied. Consequently the bioavailability of Curcumin and its antioxidant properties were analysed considering its health benefits. The best quality of turmeric in terms of Curcumin content was obtained at 46.43 % degree of starch gelatinization. The highest RSA (24%) was obtained at 5 minutes at 5 kg cm-2 pressure treatment. The correlation between degree of starch gelatinization and antioxidant property of turmeric was found to be highly negative (-0.9577).